An Optimal Planning Method for Combined Cooling Heating and Power System. (December 2016) - Chen, Peng; Guan, Lin; Tang, Zongshun; Chen, Xiaocan; Jiang, Zetao
Abstract: In this paper, a combined cooling heating and power micro-grid system framework which considers lots of device types and possible connections is presented. Based on this framework, a mathematical model considering constraints of load demand and operation is built; its optimal objective is to minimize the cost and carbon emission. The Multi-objective Particle Swarm Optimization (MPSO) method with a feedback loop is used to choose the best capacity of the equipment, and the Interior Point (IP) method algorithm is embedded in the MPSO to solve the operational optimization problem. The approach is applied to a mixed commercial and residential area of the Pearl River Delta (PRD) as a case study, verified the effectiveness of the planning method.